RELEVANT CREEDAL ISSUES HIGHLIGHTED IN THE WORKS OF IMAM MATURIDI (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
One of the most pressing issues of our time is undoubtedly the matter of takfir (excommunication). Nowadays, many extremist groups are observed to excessively accuse Muslims of disbelief, even in matters that do not constitute disbelief. According to the Maturidi creed, such actions are considered baghiyy (rebellion). In this regard, the study of Imam Maturidi's scholarly legacy and its effective application in the fight against fanaticism are of great importance.